Casos y cosas: semanario popular (Vol. 2, No. 53) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Adiós, líos conyugales..., De todo un poco, Correo franco y con...tranqueza, Las solteras y el aeroplano, Venganza femenina, Lo que piensa Fray Candil

ENGLISH: Goodbye, conjugal troubles..., A little bit of everything, Frank mail and with...tranquillity, The single women and the airplane, Female revenge, What Friar Candil thinks
Cases and things: popular weekly (Vol. 2, No. 53)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas